2020
DOI: 10.1002/lrh2.10246
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven discovery of probable Alzheimer's disease and related dementia subphenotypes using electronic health records

Abstract: Introduction: We sought to assess longitudinal electronic health records (EHRs) using machine learning (ML) methods to computationally derive probable Alzheimer's Disease (AD) and related dementia subphenotypes. Methods: A retrospective analysis of EHR data from a cohort of 7587 patients seen at a large, multi-specialty urban academic medical center in New York was conducted. Subphenotypes were derived using hierarchical clustering from 792 probable AD patients (cases) who had received at least one diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 29 publications
(49 reference statements)
3
35
0
Order By: Relevance
“…We observed a recurring cluster enriched for mental health disorders in three out of four clustering approaches. These findings highlight a clinically distinct cluster of AD patients that has been found in previous research [ 9 ] and can be a target for clinical intervention and further research. Future research should examine the best way to pick a cluster method and evaluate the results.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We observed a recurring cluster enriched for mental health disorders in three out of four clustering approaches. These findings highlight a clinically distinct cluster of AD patients that has been found in previous research [ 9 ] and can be a target for clinical intervention and further research. Future research should examine the best way to pick a cluster method and evaluate the results.…”
Section: Discussionsupporting
confidence: 76%
“…They had a faster rate of progression—roughly 3 times as fast as the other clusters, which may be driven by the earlier onset of disease. A cluster with high mental health issues was also found in a previous study subtyping AD and EHR [ 9 ], and a subtype of early onset mostly female patients was found in another [ 10 ]. The latter study also suggested that in early onset cases prodromal signs of cognitive decline can be misdiagnosed as depression.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…NACC data investigation showed that sleep disturbance, depression as well as APOE genotype are associated with subsequent diagnosis of AD dementia (Burke et al, 2016). Overall, mental health disorders are among the strong predictors of AD diagnosis, so enhancing individuals' mental health might decrease the risk of AD developing later on (Xu J. et al, 2020). Further exploration of registries data would help identifying more risk factors and how they increase the risk of dementia and hence, determining the most appropriate strategies to avoid them.…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%